2019
DOI: 10.3390/ma12091541
|View full text |Cite
|
Sign up to set email alerts
|

Parameter Study of Superabsorbent Polymers (SAPs) for Use in Durable Concrete Structures

Abstract: Superabsorbent polymers (SAPs) can be added to a concrete mixture to provide internal curing and reduce the risk for early-age shrinkage cracking. Hence, they can help to increase the overall durability of concrete structures. The type, swelling characteristics, kinetics of water release, amount and particle size of the SAPs will dictate their effectiveness for this purpose. In this paper, SAPs with different cross-linking degrees, particle sizes and amount of solubles are investigated. By varying these parame… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
22
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 41 publications
(31 citation statements)
references
References 35 publications
1
22
1
Order By: Relevance
“…The final setting time measured by penetrometer was 5.5 h for the REF mixture and 9 h for the SAP mixture. In the case of SAP addition, there is a delay in setting time, which is in accordance with earlier findings of the authors [31], and with findings reported in the literature [12,47,48].…”
Section: Fresh and Hardened Properties Of The Concrete Wallssupporting
confidence: 92%
See 1 more Smart Citation
“…The final setting time measured by penetrometer was 5.5 h for the REF mixture and 9 h for the SAP mixture. In the case of SAP addition, there is a delay in setting time, which is in accordance with earlier findings of the authors [31], and with findings reported in the literature [12,47,48].…”
Section: Fresh and Hardened Properties Of The Concrete Wallssupporting
confidence: 92%
“…In addition, Ca 2+ (or any divalent cation) can act as cross-linker which offers an additional reduction of the swelling properties; the higher the cross-linking degree, the lower the swelling capacity [28][29][30]. The evolution in time of the swelling capacity of SAPs in demineralized water and in cement filtrate for different types of SAPs and concentrations can be found in [31]. Therefore, the decrease in the swelling capacity of the SAPs used in this research at 24 h, could be linked to the additional change in the ion concentration with time of the cement filtrate solution that leads SAPs to be highly cross-linked.…”
Section: Wallsmentioning
confidence: 99%
“…At the same time, the hydration process is based on exothermic reactions causing the temperature to increase [ 22 ]. Both effects have a strong impact on the durability [ 23 ] and performance of the hardened concrete. The utilisation of SAPs can solve these problems by acting as an internal on-demand water reservoir [ 24 ].…”
Section: Introductionmentioning
confidence: 99%
“…SAP can be used as an internal curing material for low water cement ratio concrete. After absorbing water, the SAP particles become distributed uniformly in concrete, thus effectively providing the hydration water in the course of concrete hydration as well as effectively reducing the autogenous shrinkage of concrete and preventing concrete cracking [ 5 , 6 , 7 ]. SAP can also be used as an air-entraining agent, thereby improving the freeze-thaw resistance of concrete [ 8 , 9 , 10 , 11 ].…”
Section: Introductionmentioning
confidence: 99%